Evaluation of the pulmonary fellowship program of the Lung Center of the Philippines - Delos Reyes, Virginia S.
Pulmonary diseases remain to be the top causes of morbidity and mortality in the Philippines hence, there is a need to ensure that we are training competent pulmonologists to address these concerns. There is however, a lack of dependable information about the performance of educational products, practices and programs in pulmonary medicine and the absence of established systems for producing such information in the form of formal evaluation studies. This is true especially in the case of the Lung Center of the Philippines, the premier training center for pulmonologists. This study evaluated the effectiveness of the Pulmonary Fellowship of the Lung Center of the Philippines (LCP) in terms of the following: relevance to the roles and responsibilities of a pulmonologists, adequacy of resources to meet the needs of the program, appropriateness and effectiveness of teaching strategies, and contribution of its graduates in service, training and research in pulmonary medicine. The LCP Program was subjected to context, input, process, and product evaluation. All current trainees, accessible alumni, pulmonary consultants, and other key informants were included in the study population. The questionnaire given to the alumni (1985-2004) investigated the most common cases, procedures, referrals to the subspecialty, perception on the usefulness of the specific learning objectives of the program and level preparedness in these areas in their first two years of practice. The questionnaire given to pulmonary trainees (2005-2006) assessed and teaching and learning activities, competence of teachers, learning resources, implementation and overall rating of the program. Focus group discussion and key informant interviews were conducted. Pertinent documents were also reviewed. Descriptive data were summarized using frequency distribution, measures of central tendency, and variability. Data obtained from the key informant interviews, focus group discussion and documents were also correlated with the results of the questionnaires and analyzed for consistency and internal validity. Majority of the competencies and skills that were perceived to be useful by the LCP graduates in their practice were likewise those competencies that were emphasized in the LCP fellowship training program and the list of competencies given by the Philippine College of Chest Physicians. There was a good correlation between the competencies and skills perceived to be useful to the actual cases they saw in their practice. The faculty, resources, cases and procedures were adequate for the training needs of the program based on the adequacy rating by the trainees and met the minimum requirements of the accreditation board. The different rotations in general were given an above average rating in terms of clarity of training objectives, faculty supervision, relevance to students' needs and learning environment. In terms of perception of degree of preparedness in the knowledge of pulmonary diseases and commonly performed procedures, the respondents were well prepared in the most of the subspecialty areas. The mean overall rating of the program was above average. Its graduates had been recognized for their achievements in training, service and research. The LCP fellowship training program remains responsive to the needs of society in terms of adequately preparing its graduates in addressing the most common causes of respiratory morbidity and mortality in the country.